Shiva dancing on a demon - 85 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in [Multi-armed Shiva dancing on a demon has been beautifully depicted in this panel. His constant companion, Nandi can also be seen. ]